KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI KALIMANTAN UTARA TAHUN ANGGARAN 2018 - 2022 - Putri, Ferica Christinawati; Salsabila, Ananda Aprilia; Lubis, Amanda Putri Salsabila (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
North Kalimantan Province as one of the regions is required to prioritize capital expenditure to support community economic activities. The Budget Realization Report (LRA) as a form of government accountability in managing finances shows priorities on government operational expenditures. The purpose of this study is to examine the financial performance of the Regional Government of North Kalimantan Province for Fiscal Year 2018 – 2022 using 5 data analysis tools consisting of: 1) Regional Financial Independence Ratio, 2) Growth Ratio, 3) Regional Original Revenue Effectiveness Ratio, 4) Regional Financial Efficiency Ratio, and 5) Compatibility Ratio. This research includes quantitative research with a descriptive approach derived from secondary data, namely the North Kalimantan Provincial Government Budget Realization Report 2018 – 2022. The results of the study using the ratio of regional financial independence showed the value of independence classified as consultancy